Seasonal abundance and climatic determinants of Anopheles vectors in Sri Lanka: its implications in the malaria post-elimination era - Mihirini Hewavitharane; Gaya Ranawaka; M. D. J. S. Saparamadu; Risintha Premaratne; H. T. R. Jayasooriya (Malaria Journal)
Abstract Background Sri Lanka has been malaria-free since 2012, yet the risk of malaria re-introduction is high during the post-malaria elimination phase due to influx of infected individuals from endemic countries, the presence of competent Anopheles vectors, and suitable climatic conditions for vectors across Sri Lanka. This may lead to the re-emergence of autochthonous malaria in areas beyond the historically affected dry and intermediate zones. To sustain the malaria-free status, a better understanding of Anopheles species across Sri Lanka’s climatic zones is essential. This information will support the existing receptivity monitoring system. Methods Female adults of Anopheles mosquitoes were sampled monthly for two years using cattle baited trap collections (CBTC), indoor and outdoor human landing catches (HLC) and indoor hand collections (IHC), from five districts covering the dry, intermediate, and wet zones. Rainfall, temperature, and relative humidity data for the sentinel sites were obtained from the Department of Meteorology in Colombo. The study assessed Anopheles species occurrence, distribution, abundance, and densities. Spatial distribution and seasonality were analyzed using box plots, while the effects of climatic factors and collection site on malaria vectors were evaluated using negative binomial regression. Results Fifteen Anopheles mosquito species were identified, with varying abundance and densities across sites. The primary malaria vector mosquitoes were predominantly captured by HLC at all sites, except the dry zone coastal site, while secondary vectors were more common in CBTC. An. culicifacies exhibited the highest mean adult density at the intermediate zone site, with population peaks observed during the second inter-monsoon and southwest monsoon seasons at most sites, and during the northeast monsoon in the wet zone. Vector abundance was significantly influenced by climatic factors and collection site (p < 0.05); An. culicifacies densities increased with humidity, while secondary vectors showed species-specific responses to temperature, rainfall, and collection site conditions. Conclusions The spatial distribution and seasonality of Anopheles vectors provide insights on malaria vectorial efficiency in receptive areas. The intermediate zone of the island has the highest receptivity. Ongoing malaria entomological surveillance in the context of changing environmental conditions is critical for mitigating potential malaria reintroduction risks.